Efektivitas pendidikan kesehatan reproduksi terhadap peningkatan pengetahuan dan sikap pencegahan HIV/AIDS pada remaja - Sriwahyuni Sriwahyuni; Fitri H Sudiamin; Astuti Astuti; Jumrana Jumrana; Ismawati Ismawati; Firman Sugiharto (Holistik Jurnal Kesehatan, 2026)
Background: Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) remains a significant public health issue, particularly among adolescents who are vulnerable to risky behaviors due to limited knowledge and preventive attitudes. Reproductive health education is a promotive and preventive strategy with the potential to raise awareness and foster positive attitudes among adolescents toward HIV/AIDS prevention, particularly at the primary health care level, such as community health centers. Purpose: To analyze the effectiveness of reproductive health education in improving knowledge and attitudes regarding HIV/AIDS prevention among adolescents. Method: A quantitative study with a quasi-experimental approach, using a pretest-posttest design with a control group, was conducted in October 2025 at the Bontokassi Community Health Center in South Galesong. The sampling technique used purposive sampling, with a sample size of 80 participants divided into an intervention group and a control group. The independent variable in this study was reproductive health education, while the dependent variables were knowledge and attitudes. Data analysis employed univariate methods in the form of frequency distributions and bivariate analysis using the Paired T-Test. Results: Statistical analysis revealed a p-value of 0.000 (p< 0.05), indicating a significant difference between the pre- and post-intervention periods; thus, reproductive health education was found to be effective in improving participants’ knowledge and attitudes. Conclusion: Reproductive health education is effective in improving adolescents knowledge and attitudes toward HIV/AIDS prevention. This community health center-based intervention has the potential to serve as a promotive-preventive model that can be sustainably integrated into adolescent health programs in primary care settings.   Keywords: Adolescents; Attitudes; HIV/AIDS; Knowledge; Reproduction.   Pendahuluan: Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) masih menjadi masalah kesehatan masyarakat yang signifikan, terutama pada kelompok remaja yang rentan terhadap perilaku berisiko akibat rendahnya pengetahuan dan sikap pencegahan. Pendidikan kesehatan reproduksi merupakan salah satu strategi promotif dan preventif yang berpotensi meningkatkan kesadaran serta membentuk sikap positif remaja terhadap pencegahan HIV/AIDS, khususnya di tingkat layanan kesehatan primer seperti puskesmas. Tujuan: Untuk menganalisis efektivitas pendidikan kesehatan reproduksi terhadap peningkatan pengetahuan dan sikap pencegahan HIV/AIDS pada remaja. Metode: Penelitian kuantitatif dengan pendekatan quasi-eksperimental, menggunakan desain pretest-posttest with control group dilaksanakan bulan Oktober 2025 di Puskesmas Bontokassi Galesong Selatan. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel yang digunakan sebanyak 80 partisipan yang terbagi kedalam kelompok intervensi dan kelompok kontrol. Variabel independent dalam penelitian ini adalah pendidikan Kesehatan reproduksi, sedangkan variabel dependen adalah pengetahuan dan sikap. Analisis data yang digunakan univariat dalam bentuk distribusi frekuensi dan bivariat menggunakan Paired T-Test. Hasil: Uji statistik menunjukkan p-value sebesar 0.000 (p<0.05), yang berarti terdapat perbedaan yang signifikan antara sebelum dan sesudah intervensi, sehingga pendidikan kesehatan reproduksi terbukti efektif dalam meningkatkan pengetahuan dan sikap partisipan. Simpulan: Pendidikan kesehatan reproduksi efektif meningkatkan pengetahuan dan sikap remaja terhadap pencegahan HIV/AIDS. Intervensi berbasis Puskesmas ini berpotensi menjadi model promotif-preventif yang dapat diintegrasikan secara berkelanjutan dalam program kesehatan remaja di layanan primer.   Kata Kunci: HIV/AIDS; Pengetahuan; Remaja; Reproduksi; Sikap.